Determination of Important Building Construction Adverse Impacts Creating Nuisances in Residential Areas on Neighbouring Community - Budayan, Cenk; Celik, Tolga (TURKISH CHAMBER CIVIL ENGINEERS, 2021)
The construction industry is criticized due to poor stakeholder management. Whereas, the stakeholders play important roles in the completion of construction projects in line with their concerns and needs. Therefore, it is crucial to identify and incorporate the needs and concerns of the stakeholders during management applications for the commercial success of a construction project. For that purpose, in this study, the adverse impacts of the building constructions in residential areas which create nuisances on one of the external stakeholders, namely neighbouring community, are aimed to be identified. Thus, a questionnaire survey is performed with 266 respondents neighbouring building constructions in different cities of Northern Cyprus. A model based on the adverse impacts of building constructions and their categories is proposed, and this model is analysed using structural equation modelling (SEM). The results of the participants reveal that the entire adverse impacts are perceived as contributing causes for a disturbance on the neighbouring community. Last but not least, conducted research highlights that the social and cultural manners of the society which shows variations from region to region plays a significant role in the way community absorbs and experiences these adverse impacts.
Keywords: Construction projects; neighbouring community; nuisances; stakeholder management; structural equation modelling; SOCIAL COST; PROJECTS; INFRASTRUCTURE; MODEL; FIT; Engineering